Aerobic Oil-Phase Cyclic Magnetic Adsorption to Synthesize 1D Fe(2)O(3)@TiO(2) Nanotube Composites for Enhanced Visible-Light Photocatalytic Degradation - Tao, Qingqing (Nanomaterials (Basel), 2020)
In this work, Fe(2)O(3)@TiO(2) nanostructures with staggered band alignment were newly designed by an aerobic oil-phase cyclic magnetic adsorption method. XRD and TEM analyses were performed to verify the uniform deposition of Fe(2)O(3) nanoparticles on the nanotube inner walls of TiO(2). The steady-state degradation experiments exhibited that 1FeTi possessed the most superior performance, which might be ascribable to the satisfying dark adsorption capacity, efficient photocatalytic activity, ease of magnetic separation, and economic efficiency. These results indicated that the deposition of Fe(2)O(3) into TiO(2) nanotubes significantly enhanced the activity of Fe(2)O(3), which was mainly ascribed to the Fe(2)O(3)-induced formation of staggered iron oxides@TiO(2) band alignment and thus efficient separation of h(+) and e(−). Furthermore, the PL intensity and lifetime of the decay curve were considered as key criterions for the activity’s evaluation. Finally, the leaching tests and regeneration experiments were also performed, which illustrated the inhibited photodissolution compared with TiO(2)/Fe(3)O(4) and stable cycling ability, enabling 1FeTi to be a promising magnetic material for photocatalytic water remediation.